Faktor - Faktor Yang Berhubungan Dengan Hipertensi Pada Usia Dewasa - Ekarini, Ni Luh Putu; Wahyuni, Jathu Dwi; Sulistyowati, Dita (Jurnal Keperawatan, 2020)
Hypertension is a non-communicable disease with an increasing number of events every year. There are two risk factors for hypertension, namely risk factors that cannot be modified, such as age, sex and genetics, and modifiable risk factors such as obesity, smoking, lack of physical activity, excessive salt consumption, dyslipidemia, alcohol consumption and psychososis and stress. This study aims to obtain an overview of the factors associated with hypertension in adulthood. The research design used was descriptive analytic research with cross-sectional studies. The number of samples is 70 people with simple random sampling technique. Data analysis used univariate, bivariate (chi square) and multivariate (multiple logistic regression) component analyzes. Multivariate analysis showed that the variable that was significantly related to the occurrence of hypertension was the age variable (pvalue = 0.009). Variable overweight and physical activity as confounding variables. The analysis results obtained OR from the age variable is 2.9, meaning that patients in middle to upper adult age will experience hypertension 2.9 times higher than young adult patients after being controlled by obesity and physical activity variables. Recommendations from the results of this study are expected to be able to provide health care institutions that emphasize the promotive and preventive aspects of patients who have a history of hypertension.